Tinjauan Kejelasan Dan Kelengkapan Penulisan Diagnosa Dalam Ketepatan Kode Sistem Cardiovascular Pasien Rawat Inap Di Rumah Sakit Islam Ibnu Sina Padang - Sari, Dian; Maisharoh; Friska Nurul Fitria (Sekolah Tinggi Ilmu Kesehatan YPAK Padang, 2025)
Diagnosis coding is the activity of assigning disease codes using letters or numbers or a combination of letters and numbers that represent data components. Based on a survey of 10 medical record documents, there were 2 medical records that did not correctly code the diagnosis. The purpose of this study was to determine the Review of Clarity and Completeness of Diagnosis Writing in the Accuracy of Cardiovascular System Codes for Inpatients at Ibnu Sina Islamic Hospital Padang. The research was conducted quantitatively with a descriptive approach. sampling using Accidental sampling technique and using the Lameshow formula. Data collection was done by observation and data processing techniques editing, coding, Entry, and cleaning. The analysis used was univariate analysis. The results of the study found, from 96 medical records, 11.5% of diagnosis writing was unclear, 42.7% of diagnosis writing was incomplete and 30.2% of diagnosis codes were inaccurate. The conclusion is that there is still inaccurate coding in medical records due to factors of clarity and completeness of diagnostic writing, so it is hoped that health workers will complete and write clearly the diagnosis of the disease so that it can make it easier to provide diagnostic codes.